The altitudinal distribution characteristics of functional traits reflect the resource allocation strategy of Abies georgei var. smithii in southeast Tibet - Wang, Chao; Duan, Fei; Zhou, Chenni; Lu, Jie (Frontiers in Ecology and Evolution, 2023)
To explore the adaptation strategies of the above-ground and underground functional traits of alpine plants on the altitude gradient, a typical stand of primitive dark coniferous forests in southeast of Tibet-Abies georgei var. smithii was taken as the research object in the present study. The variation characteristics of the functional traits of leaves, current-year twigs, trunks and fine roots in 6 continuous altitude gradients and the relationships between functional traits and environmental factors were explored. It is of paramount significance for exploring the essence of terrestrial ecosystems and their functional processes in in extreme high-altitude environments. The results showed that soil organic carbon (SOC) may exert a positive effect on the construction of plant defense tissue via the change of functional traits; altitude (Alt) represents the primary influencing factor of wood density (WD) variation; particulate organic carbon (POC) content mainly affected fine root dry matter (RDWC) content and specific root length (SRL), total potassium (TK) content was the main factor that affected fine root tissue density (RTD). Leaves, current-year twigs, and fine roots exhibited high production or nutrient acquisition capacity at the altitude of 4,000 m, and also show strong defense and relatively stable water and nutrients transport capacity. The ecological strategy of Abies georgei var. smithii in Sejila Mountain was more conservative. Plus, the optimal survival area of Abies georgei var. smithii was located at 4,000 m on shady slope of Sejila Mountain.